2022
DOI: 10.1088/1741-4326/aca91d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope plasma-driven permeation through RAFM steel: isotope exchange and helium irradiation effect

Abstract: Hydrogen isotope exchange in CLAM steel was investigated by plasma-driven permeation measurements in the temperature range of ~670-920 K. It was found that as introducing H into D plasma, the permeation flux of HD increased while that of D2 decreased. The total D permeation flux, however, remained almost unchanged. Such a result allowed the analysis of isotope replacement and showed that the reduction of D2 is balanced by the rise of HD. In addition, the formation of HD was found to be closely related to the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several excellent experimental studies have demonstrated that isotope exchange can effectively remove retained HIs [21][22][23][24][25][26][27][28][29][30]. Schwarz-Selinger and Alimov et al [23,24] implanted D and H plasma sequentially into W. They observed strong isotope exchange appeared near the W surface at room temperature, while extended to all depths at elevated temperatures, achieving up to 90% removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent experimental studies have demonstrated that isotope exchange can effectively remove retained HIs [21][22][23][24][25][26][27][28][29][30]. Schwarz-Selinger and Alimov et al [23,24] implanted D and H plasma sequentially into W. They observed strong isotope exchange appeared near the W surface at room temperature, while extended to all depths at elevated temperatures, achieving up to 90% removal efficiency.…”
Section: Introductionmentioning
confidence: 99%